Exercise-Induced Irisin, the Fat Browning Myokine, as a Potential Anticancer Agent - Maalouf, George-Emmanuel (J Obes, 2019)
Irisin is a recently discovered myokine that plays an important role in fat metabolism through the browning of white adipose tissue. This myokine is usually secreted after exercise by improving energy balance and has shown great potential as a possible treatment for some metabolic diseases such as obesity, insulin resistance, and inflammation. Obesity has been linked to a higher incidence of some cancers. Furthermore, some studies have shown irisin to have direct positive effects on different types of cancers. Although it is hard to relay conclusions from in vitro to in vivo studies, the majority of the available data favor irisin as a potential substance for cancer regression through reducing proinflammatory markers linked to obesity. However, some controversies remain on the exact benefits of irisin on cancer with some studies showing no or even a negative effect of irisin on cancer. This review summarizes these 2 differing viewpoints and synthesizes them to form a clearer picture of exercise-induced irisin's effects on cancer.